The international trauma questionnaire (ITQ) measures reliable and clinically significant treatment-related change in PTSD and complex PTSD. Issue 1 (1st January 2021) - Cloitre, Marylène; Hyland, Philip; Prins, Annabel; Shevlin, Mark
ABSTRACT: Background : The International Trauma Questionnaire (ITQ) is a validated measure that assesses ICD-11 posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD). An important task is to determine whether the ITQ is an appropriate evaluative measure for clinical trials. Objective : To assess the psychometric properties of the ITQ in the context of treatment and determine if the ITQ measures reliable and clinically significant change over the course of a psychosocial intervention. Method : Analyses were based on data from an online skills training programme delivered to 254 U.S. Veterans. Reliability and validity of the ITQ scores were assessed at baseline. Changes in symptom scores and probable diagnostic rates were compared at pre-, mid- and post-treatment. A reliable change index (RCI) score was computed to classify participants as improved, unchanged, or worsened. The PCL-5 was used as a comparison measure. Results : Baseline concurrent and factorial validity was similar to previous studies. Internal consistency at each assessment was excellent and comparable to the PCL-5. Decline in symptoms from pre-to-post-treatment was significant for PTSD and CPTSD symptom profiles. Rate of probable disorder (PTSD or CPTSD) declined significantly from pre-treatment to post-treatment. Pre-to-post treatment declines exceeded the critical RCI values for the ITQ. Clinically significant changes were observed where most participants improved, some stayed the same, and few worsened. The performance of the ITQ was consistent with the PCL-5 regarding sensitivity to change. Conclusion : This study provides the first demonstration that the ITQ measures reliable and clinically significant treatment-related change of ICD-11 PTSD and CPTSD symptoms. HIGHLIGHTS: This study provides the first demonstration that the International Trauma Questionnaire (ITQ) measures reliable and clinically significant treatment-related change in ICD-11 PTSD and Complex PTSD.